Feeding Biology of Pectoral Sandpiper Calidris Melanotos (Birds: Scolopacidae) In the Floodplain of the Paraná River, Argentina - Bagnarol, Mónica (2010)
This study focuses upon the nourishing biology of the Pectoral Sandpiper at the floodplain of the Paraná river during  spring and summer. Trophic spectrum, feeding selectivity and efficiency, extent of the trophic niche, circadian rhythm of feeding activity, size of preys and habitat preference were evaluated. Twenty eight stomachs were analyzed Containing twenty-seven taxonomic entities: 12 were vegetal 15 animal. The highest index’s values of relative importance were for seeds and coleoptera; showing this a generalist diet. The amplitude of the trophic niche remined constant along the studied periodFeeding was more active during early morning hours. The more frequent prey size were between 1.5 and 5 mm .The habitat preference index was registered only for the beach (Pi=0.7). This work constitutes the first contribution to knowledge of this species feeding ecology in this region.